Subjective Experience of Antidepressant Prescription Among Adolescents With Anorexia Nervosa - Ludot-Grégoire, Maude; David, Vanille; Carretier, Emilie; Lachal, Jonathan; Moro, Marie Rose; Blanchet, Corinne (Frontiers in Psychiatry, 2022)
Introduction: Major depressive disorder is considered the most common comorbidity of anorexia nervosa in adolescence. Some evidence argues against antidepressant use in this population. Moreover, the fear of being threatened with autonomy and of becoming dependent specific to the adolescent population and at the very core of the anorexic disease, make the proposal of such a treatment difficult to accept. This qualitative research aimed to explore the perspectives of view of adolescents with anorexia nervosa about antidepressants. Methods: We conducted interviews with adolescents suffering from anorexia nervosa who had been treated with an antidepressant agent during their inpatient or outpatient care at Cochin Hospital. Both verbal and written questions were asked to elicit their lived experiences. Interpretative Phenomenological Analysis was used to examine the data. Results: Fifteen adolescents (thirteen boys and two girls) were interviewed. We have reached total data saturation. The analysis found two meta-themes, each with two separate themes. (I) Reactions to the proposal of antidepressant with (i) an opposition phase (about the existence of depressive symptoms and about negative preconceptions) and (ii) need to share with family and other teenagers. (II) Reactions to antidepressant use with (iii) ambivalence and an initial perception of coercion, and (iv) effects of antidepressants (psychological effects, effects on the body and on anorexia nervosa and effects perceived through the eyes of others). Discussion: Despite positive effects, ambivalence towards the treatment remained present throughout the interviews: these adolescents still worry greatly about loss of control and weight gain. Depression as comorbidity seems to be entangled in the denial of the disease, cognitive distortion and acquired fearlessness specific to AN. Its existence in adolescence can uncover transgenerational issues, sometimes previously hidden. An orodispersible/drinkable form of antidepressants would facilitate adherence to treatment in this specific population. The intervention of a "patient-expert" could reduce adolescents' anxiety about loss of control. A latency period seems necessary to allow them to understand the prescription at their own level and in the complexity of their anorexic illness.